Phenol electrolyte for electrolytic aqueous zinc-manganese battery, preparation method of phenol electrolyte and application of phenol electrolyte in soft package battery

By using phenol electrolytes in aqueous zinc-manganese batteries, the electrolyte ratio is regulated, and the dissolution and deposition mechanism of manganese dioxide with dual electron transfer is achieved, the problem of discharge capacity loss and cycle instability of the battery under high surface capacity density is solved, the discharge capacity and cycle stability of the battery are improved, and the low-cost and environmentally friendly and safe battery preparation is achieved.

CN119627267AActive Publication Date: 2025-03-14CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510041262.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-14
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The discharge capacity of aqueous zinc-manganese batteries still suffers a large loss compared to the charging capacity under high surface capacity density, and the circulation is unstable, which limits its large-scale application.

Method used

A phenol electrolyte for electrolytic aqueous zinc-manganese battery is designed. By regulating the electrolyte ratio, the battery can achieve a stable dual electron transfer manganese dioxide dissolution and deposition mechanism, and improve the reversibility of the positive electrode reaction and the compatibility of the zinc-negative electrode.

Benefits of technology

The discharge capacity and cycle stability of water-based zinc-manganese batteries have been improved, and the long cycle performance has been improved. The battery preparation cost is low, the process is short, and the materials are environmentally friendly and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627267A_ABST
    Figure CN119627267A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, and provides a phenol organic matter additive electrolyte for an aqueous zinc-manganese battery, which is convenient to produce, suitable in price and non-toxic, and the electrolyte is composed of a mixed aqueous solution of manganese acetate, zinc acetate, potassium chloride and a phenol organic matter, wherein the phenol organic matter additive serves as a redox medium to participate in the electrochemical reaction process of the positive electrode, dissolution of manganese dioxide in the discharging process is promoted, high positive electrode reaction reversibility is achieved, and the long cycle performance of the water-based zinc-manganese battery is improved; the invention also provides a soft package battery device structure design based on a manganese dioxide dissolution and deposition mechanism, and the energy storage application process of the aqueous zinc-manganese battery based on the manganese dioxide dissolution and deposition mechanism is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary batteries, in particular to the technical field of electrolytic aqueous zinc-manganese secondary batteries, and particularly designs a phenol electrolyte for electrolytic aqueous zinc-manganese batteries, a preparation method thereof, and soft-pack battery applications. Background Art

[0002] In order to cope with the increasingly serious problems of energy shortage and environmental pollution, the development of renewable energy and its related large-scale energy storage technology is one of the key tasks to be solved worldwide. Among them, secondary batteries, as a high-efficiency electrochemical energy storage technology, have received widespread attention from the scientific and industrial communities. Although non-aqueous lithium-ion batteries dominate the fields of portable electronic devices and electric vehicles, flammable organic electrolytes make them face serious safety issues. Aqueous zinc-manganese batteries have more outstanding advantages than other energy storage technologies due to their low cost, environmental protection, high safety, simple preparation, and high conversion efficiency. The development of green and safe secondary batteries is the key to developing new electrochemical energy storage systems and optimizing the energy supply structure.

[0003] Among them, aqueous zinc-manganese batteries have attracted much attention due to their low cost, high voltage, and large theoretical capacity. + / Zn 2+ The intercalation mechanism of manganese dioxide (MnO2) cathode has been reported and studied intensively, however, the lower Mn 3+ / Mn 4+ The conversion reaction kinetics and the capacity decay caused by the structural collapse of the manganese dioxide positive electrode active material during the cycle in a weak acid electrolyte environment limit the large-scale application of secondary zinc-manganese batteries. In recent years, aqueous zinc-manganese batteries based on the MnO2 deposition / dissolution reaction mechanism of double electron transfer have begun to attract attention. Compared with the single electron reaction of the conventional neutral zinc-manganese battery, the zinc-manganese battery based on the MnO2 deposition / dissolution mechanism has a high theoretical capacity (616 mAh g) due to its double electron transfer in the positive electrode reaction. -1 ). In addition, water Mn 2+ The reversible solid / liquid conversion reaction mechanism in / MnO2 batteries can release the pressure of structural collapse and achieve long-term high-efficiency cycle stability. 2+ / MnO2-based aqueous zinc-manganese battery has a simple assembly process and is one of the aqueous batteries with great potential for large-scale energy storage.

[0004] However, Mn 2+ / MnO2-based aqueous zinc-manganese batteries still face huge challenges in practical application. The most fundamental reason is that the Mn 2+ Mn / MnO2 conversion process 3+The poor reaction kinetics caused by disproportionation makes it extremely challenging to achieve a reversible and efficient cathode reaction. 2+ Aqueous zinc-manganese flow batteries that perform the / MnO2 conversion reaction rely on expensive ion exchange membranes to maintain the normal operation of the battery, which will greatly increase the manufacturing cost of the battery. 2+ The electrolyte engineering of reversible Zn / MnO2 conversion and high zinc anode compatibility is the key challenge to realize aqueous zinc-manganese battery with high specific energy, long life and low cost.

[0005] Fujian Institute of Research on the Structure of Matter, Chinese Academy of Sciences proposed an electrolytic zinc-manganese aqueous battery in CN 118198527 A, the electrolytic zinc-manganese aqueous battery comprising a positive electrode, a zinc metal negative electrode and an electrolyte; the electrolyte comprising a manganese salt, a zinc salt, water, an acid and an electrolyte additive; the electrolyte additive is hydroxymethyl (sub)dimethyl phosphite. The present invention uses the synergistic effect of hydroxyl and phosphate groups in hydroxymethyl (sub)dimethyl phosphite to induce the electrolytic effect. Since the phosphorus-oxygen double bond (PO) in the phosphate group can open the metal manganese and zinc cations in the complex electrolyte, they can quickly migrate to the electrode electrolyte interface under the guidance of the hydroxyl group to perform an electrochemical redox reaction, thereby facilitating the deposition and dissolution chemistry of manganese dioxide and zinc cations and catalyzing the electrolytic reaction kinetics. A solution is proposed for the problem of poor electrochemical dissolution kinetics of manganese dioxide in the discharge process of electrolytic aqueous zinc-manganese batteries, but the battery still has a large loss in discharge capacity relative to charging capacity at a high surface capacity density (11.95mAh cm -2 The discharge capacity is compared to 15 mAh cm -2 of charging capacity).

[0006] The University of Science and Technology of China proposed an aqueous composite mechanism zinc-manganese battery in CN 116525973 A, including: a positive electrode, a negative electrode and an electrolyte system. The positive electrode includes an electrode material loaded with manganese dioxide, wherein the first part of the manganese dioxide as an active material undergoes insertion / extraction reactions with hydrogen ions and zinc ions, and the second part of the manganese dioxide undergoes a deposition and dissolution reaction. The negative electrode includes a conductive current collector material to achieve the redox reaction of zinc ions and zinc elements. The electrolyte system includes a mixed solution of zinc salt, manganese salt and pH regulating solution. Among them, the charging and discharging conditions of the battery include: the charging cut-off voltage range includes 1.99~2.2V, so as to satisfy the simultaneous insertion and extraction reactions and deposition and dissolution reactions. During the composite process, the MnO2 deposited and dissolved at the positive electrode not only directly contributes to the battery capacity, but also can participate in the Zn 2+ and H + The insertion / extraction reaction contributes additional capacity through single electron transfer, which not only increases the capacity of the battery but also ensures the working stability of the battery.

[0007] Central South University proposed a colloidal electrolyte for aqueous zinc-manganese batteries in CN 118099557 A, including a solvent and an electrolyte, wherein the solvent is water, the electrolyte contains zinc salt, manganese salt, additives and organic acid / inorganic acid that provides additional protons when MnO2 dissolves, wherein the additives include gelling agent and ferrous sulfate, the mass of the gelling agent accounts for 5-12.5% ​​of the mass of the electrolyte, and the molar concentration of ferrous sulfate is 0.005-0.02 mol / L. This patent uses colloid as a promoter for the charging and deposition process of manganese dioxide, and ferrous sulfate as a dissolution promoter for the discharge process of manganese dioxide to participate in the electrode reaction process. Among them, ferrous ions will corrode the negative electrode, and the additional sulfuric acid also causes severe corrosion of the negative electrode. However, this patent uses phenolic compounds with better compatibility with zinc negative electrodes. Therefore, this patent can be used as an application of electrolytic zinc-manganese soft-pack batteries in a closed system.

[0008] The University of Science and Technology of China disclosed an aqueous electrolyte and an aqueous electrolytic MnO2-Zn battery in CN 113054264 B. The aqueous electrolytic MnO2-Zn battery comprises: an electrolyte comprising a zinc salt, a manganese salt and a liquid redox medium, wherein the electrolyte is an acidic electrolyte; a positive electrode for reacting with the electrolyte to react MnO2 / Mn 2+ A negative electrode for conducting a Zn-reduction reaction with the electrolyte. 2+ / Zn redox reaction. This patent uses iodine salt, bromine salt, and vanadium salt as redox medium additives. These additives cause corrosion of the zinc negative electrode and are not suitable for soft-pack battery systems. And the kinetic performance itself is poor, which affects the battery cycle performance. This patent uses phenol compounds that have better compatibility with the zinc negative electrode and faster electrode reaction kinetics. Therefore, this patent can be used as a closed system zinc-manganese soft-pack battery.

[0009] Therefore, how to improve the discharge capacity of aqueous zinc-manganese batteries and maintain their cycle stability has become a hot topic in current research. Summary of the invention

[0010] In order to solve the deficiencies and shortcomings of the above-mentioned prior art, the purpose of the present invention is to propose an aqueous zinc-manganese battery based on a phenol additive electrolyte, which realizes the manganese dioxide dissolution and deposition mechanism process of stable double electron transfer in the battery by designing and regulating the electrolyte ratio, and improves technical problems such as low positive capacity and unstable cycle of aqueous zinc-manganese batteries.

[0011] A phenol electrolyte for an electrolytic aqueous zinc-manganese battery, wherein the electrolyte is composed of zinc acetate, manganese acetate, potassium chloride and a mixed aqueous solution of phenol organic matter, wherein the concentrations of the components are: 0.5-3 mol / L of manganese acetate, 0.5-2 mol / L of zinc acetate, 1-3 mol / L of potassium chloride, and 0.0005-0.01 mol / L of phenol organic matter, and the phenol organic matter is one or more of hydroquinone, 2-methylhydroquinone, 2,6-dimethylhydroquinone, 2,3,5-trimethylhydroquinone, tert-butylhydroquinone, 2-methoxyhydroquinone and 2,5-dihydroxybiphenyl.

[0012] Preferably, the concentrations of the components are: 1 mol / L zinc acetate, 1.5 mol / L manganese acetate, 2 mol / L potassium chloride and 0.002 mol / L phenolic organic matter.

[0013] A method for preparing the above-mentioned phenol electrolyte for electrolytic aqueous zinc-manganese battery, characterized in that it comprises the following steps:

[0014] 1) adding deionized water to a mixture of manganese acetate, zinc acetate and potassium chloride to obtain solution A;

[0015] 2) adding deionized water to the phenol compound powder to obtain solution B;

[0016] 3) ultrasonically dispersing solution A and solution B to obtain a clear solution;

[0017] 4) A certain amount of solution B is added to solution A, and the mixture is mixed and dispersed uniformly to obtain solution C; solution C is a phenol electrolyte for electrolytic aqueous zinc-manganese batteries.

[0018] The above-mentioned phenol electrolyte for electrolytic aqueous zinc-manganese battery is used in soft-pack batteries.

[0019] As a preference, the method comprises the following steps:

[0020] 1) preparing a positive electrode sheet;

[0021] 2) Preparation of zinc negative electrode sheet:

[0022] 3) Preparing a soft-pack battery: adding a phenol electrolyte for an electrolytic aqueous zinc-manganese battery into a glass fiber separator to obtain a separator with added electrolyte, and matching it with a negative electrode sheet, a positive electrode sheet, a titanium foil, a heat shrinkable film and an aluminum-plastic film. The assembly and stacking order is a negative electrode sheet, a separator with added electrolyte, a positive electrode sheet, a titanium foil, a positive electrode sheet, a separator with added electrolyte, and a negative electrode sheet to obtain a single cell of a zinc-manganese soft-pack battery. Then, the cell is packaged with an aluminum-plastic film to prepare a soft-pack battery.

[0023] Preferably, the preparation of the positive electrode sheet comprises: preparing a dispersion A of conductive carbon and polyvinylidene fluoride binder in N-methylpyrrolidone; wherein the mass ratio of the conductive carbon to the polyvinylidene fluoride binder is (1-20):1, and the mass ratio of the solute to the solvent in the dispersion A is 1 / 50 to 1 / 70; dropping the dispersion A into the positive electrode carbon material until saturated, and drying until the dispersion solvent N-methylpyrrolidone is completely removed to obtain a positive electrode;

[0024] The conductive carbon includes one or more of activated carbon, carbon micron, nanofiber, carbon nanotube, carbon sphere, Ketjen black and conductive carbon black;

[0025] The positive electrode carbon material is one or more of carbon felt, graphite felt, graphite, graphene, carbon cloth, and carbon paper.

[0026] Preferably, the method of preparing the zinc negative electrode sheet is: cutting commercial foil to obtain a zinc metal negative electrode sheet.

[0027] The soft-pack battery is obtained by applying the phenol electrolyte for the above-mentioned electrolytic aqueous zinc-manganese battery to the soft-pack battery.

[0028] Compared with the prior art, the beneficial effect is

[0029] (1) The present invention provides an electrolyte additive that is easy to produce and has a suitable price. The phenol compound is reacted with Mn 2+ / MnO2 positive electrode reaction, promotes the dissolution stage of MnO2 during discharge, realizes highly reversible positive electrode reaction, and improves the long cycle performance of aqueous zinc-manganese battery. The optimal embodiment can achieve 95% capacity retention rate after 240 cycles (capacity retention rate = 230th cycle capacity / maximum capacity within 230 cycles).

[0030] (2) The present invention provides a soft-pack battery structure of an electrolytic aqueous zinc-manganese battery based on the dissolution and deposition reaction of manganese dioxide. Compared with other electrolytic aqueous zinc-manganese batteries, this soft-pack battery structure has the advantages of low preparation cost, short preparation process, and easy preparation process, which is conducive to promoting the application of electrolytic aqueous zinc-manganese batteries.

[0031] (3) Compared with the existing battery system, the electrolytic aqueous zinc-manganese battery electrolyte provided by the present invention has the advantages of low-cost raw materials, simple preparation, and no toxic heavy metal elements such as lead, cadmium, and vanadium. It has the advantages of environmental protection and safety.

[0032] (4) Compared with the existing battery system, the aqueous zinc-manganese battery electrolyte provided by the present invention does not require additional acid additives (sulfuric acid, acetic acid, phosphoric acid, etc.), and compared with the existing electrolyte additives such as Fe that promote the dissolution of manganese dioxide during the discharge process of electrolytic aqueous zinc-manganese batteries, 2+ Cr 3+,I - Br - Etc., phenol compounds have better compatibility with zinc metal negative electrode, which prevents the corrosion of zinc metal negative electrode by additives and prolongs battery life.

[0033] According to the embodiments of the present invention, a large number of experiments are conducted to verify the feasibility of phenol compounds promoting the dissolution of manganese dioxide during the discharge stage, and the results show that by adding phenol compounds to the electrolyte, the battery system can be regulated to perform highly reversible Mn 2+ / MnO2 double electron transfer, that is, manganese dioxide itself undergoes a double electron transfer deposition / dissolution reaction and is applied to soft-pack batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 The voltage curve and positive electrode reaction schematic diagram of the battery system using phenol electrolyte of the present invention;

[0036] Figure 2 This is a schematic diagram of the assembly of a soft-pack battery using a phenolic additive electrolyte according to the present invention;

[0037] Figure 3 This is a Fourier infrared test result diagram of the electrolyte in Example 1 of the present invention before and after adding manganese dioxide powder;

[0038] Figure 4 The figure is a comparison chart of the cycle performance of Example 1, Example 2 and Comparative Example 1 in the present invention;

[0039] Figure 5 This is a comparison chart of the cycle performance of Example 3, Example 4 and Example 5 of the present invention;

[0040] Figure 6 This is a comparison chart of the cycle performance of Example 6, Example 7 and Example 8 of the present invention;

[0041] Figure 7 This is a cycle performance diagram of Example 9 of the present invention;

[0042] Figure 8 This is a voltage capacity diagram of Example 9 of the present invention;

[0043] Fig. 9 1 is a cycle performance diagram of Example 10 of the present invention;

[0044] Fig.10 This is a voltage capacity diagram of Example 10 of the present invention; DETAILED DESCRIPTION

[0045] In order to enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention and to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are further described below.

[0046] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0047] The battery positive electrode reaction mechanism diagram provided by the present invention is as follows Figure 1 As shown:

[0048] Charging process:

[0049] Mn 2+ +2H2O=MnO2+4H + +2e -

[0050] Discharge process 1:

[0051] MnO2+4H + +2e - =Mn 2+ +2H2O

[0052] Discharge process 2:

[0053] C6H4O2+2H + +2e - =C6H6O2

[0054] C6H6O2+MnO2+2H + =Mn 2+ +C6H4O2+H2O

[0055] Example 1

[0056] 1) Preparation of Example 1 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L hydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.11 g hydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a hydroquinone additive electrolyte.

[0057] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​25 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0058] 3) Preparation of zinc negative electrode sheet: Cut the commercial zinc foil into a sheet with an area of ​​27 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0059] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (25 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 27cm 2 ), heat shrink film, aluminum plastic film Figure 2 The battery is assembled by stacking the zinc negative electrode, separator (with electrolyte added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (with electrolyte added), and zinc negative electrode in this order, and then putting them into a heat shrink film for heating so that the heat shrink film is tightly attached to the battery cell and then sealed in an aluminum-plastic film to obtain a soft-pack battery. Figure 2 shown.

[0060] 5) Study on the reaction mechanism of electrolyte phenol compounds: The electrolyte solution A in Example 1 and the electrolyte dispersion B in Example 1 with added manganese dioxide powder were tested by Fourier transform infrared spectroscopy. The results are as follows: Figure 3 The results show that manganese dioxide reacts with phenolic compounds and converts phenolic compounds into benzoquinone compounds.

[0061] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, at 4mA / cm 2 The soft pack battery was tested at a current density of Figure 4 As shown in Example 1.

[0062] Example 2

[0063] 1) Preparation of Example 2 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L tert-butylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.166 g tert-butylhydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a tert-butylhydroquinone additive electrolyte.

[0064] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​25 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0065] 3) Preparation of zinc negative electrode sheet: Cut the commercial zinc foil into a sheet with an area of ​​27 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0066] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (25 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 27cm 2 ), heat shrink film, aluminum plastic film Figure 2 The battery is assembled by stacking the zinc negative electrode, separator (electrolyte has been added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (electrolyte has been added), and zinc negative electrode in this order, and then putting them into a heat shrinkable film for heating so that the heat shrinkable film can fit and fix the battery cell tightly, and then sealing it in an aluminum-plastic film to obtain a soft-pack battery.

[0067] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, at 4mA / cm 2 The soft pack battery was tested at a current density of Figure 4 As shown in Example 2, after 240 cycles, the capacity retention rate can reach 95%, and the capacity retention rate = (240th cycle capacity / maximum capacity within 240 cycles). This illustrates the role of tert-butyl additive electrolyte in promoting the cycle performance of aqueous zinc-manganese batteries.

[0068] Example 3

[0069] 1) Preparation of Example 3 electrolyte (concentrations of 1 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 12.2 g manganese acetate and 7.45 g potassium chloride to obtain 1 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.138 g 2,6-dimethylhydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a 2,6-dimethylhydroquinone additive electrolyte.

[0070] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​80 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0071] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut into pieces with an area of ​​84 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0072] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (80 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 84cm 2 ), heat shrink film, aluminum plastic film Figure 2 The battery is assembled by stacking the zinc negative electrode, separator (with electrolyte added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (with electrolyte added), and zinc negative electrode in this order, and then putting them into heat shrink film for heating, so that the heat shrink film can tightly fit and fix the battery core to obtain a single-layer battery core. The single battery core is stacked and put into aluminum-plastic film to obtain a soft-pack battery.

[0073] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, the soft pack batteries were tested at a charging current of 0.6C and a discharge current density of 0.2C. The test results are as follows: Figure 5 As shown in Example 3.

[0074] Example 4

[0075] 1) Preparation of Example 4 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.138 g 2,6-dimethylhydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a 2,6-dimethylhydroquinone additive electrolyte.

[0076] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​80 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0077] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut into pieces with an area of ​​84 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0078] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (80 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 84cm 2 ), heat shrink film, aluminum plastic film Figure 2 The battery is assembled by stacking the zinc negative electrode, separator (with electrolyte added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (with electrolyte added), and zinc negative electrode in this order, and then putting them into a heat shrinkable film for heating so that the heat shrinkable film is tightly attached to the battery cell to obtain a single-layer battery cell. The single battery cells are stacked and packaged in an aluminum-plastic film to obtain a soft-pack battery.

[0079] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, the soft pack batteries were tested at a charging current of 0.6C and a discharge current density of 0.2C. Figure 5 As shown in Example 4. Compared with Example 3 and Example 5, Example 4 has the longest cycle life, indicating that the optimal concentration of manganese ions in the electrolyte is 1.5 mol / L.

[0080] Example 5

[0081] 1) Preparation of Example 5 electrolyte (concentrations of 2 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 24.4 g manganese acetate and 7.45 g potassium chloride to obtain 2 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.138 g 2,6-dimethylhydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a 2,6-dimethylhydroquinone additive electrolyte.

[0082] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​80 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0083] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut into pieces with an area of ​​84 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0084] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (80 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 84cm 2 ), heat shrink film, aluminum plastic film Figure 2 The battery is assembled by stacking the zinc negative electrode, separator (with electrolyte added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (with electrolyte added), and zinc negative electrode in this order, and then putting them into a heat shrinkable film for heating so that the heat shrinkable film is tightly attached to the battery cell to obtain a single-layer battery cell. The single battery cells are stacked and packaged in an aluminum-plastic film to obtain a soft-pack battery.

[0085] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, the soft pack batteries were tested at a charging current of 0.6C and a discharge current density of 0.2C. The results are as follows: Figure 5 As shown in Example 5.

[0086] Example 6

[0087] 1) Preparation of Example 6 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.001 mol / L 2,6-dimethylhydroquinone): 49 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.110 g hydroquinone powder to obtain solution B. 1 mL of solution B was added to solution A to obtain a hydroquinone additive electrolyte.

[0088] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an active area of ​​1 cm -2 , thickness is 6mm on graphite felt, conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0089] 3) Preparation of zinc negative electrode sheet: Cut commercial zinc foil into pieces with an active area of ​​1 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0090] 4) Preparation of static electrolytic cell: The electrolyte of Example 6 prepared above was added into the electrolytic cell. The positive electrode sheet and the zinc negative electrode sheet were respectively mounted on the platinum metal electrode clips to obtain a static electrolytic cell.

[0091] 5) Static electrolytic cell battery test: Using the Xinwei battery test system, at 10mA / cm 2 , 10mAh / cm 2 The static electrolyzer battery was tested under the charge and discharge regime, such as Figure 6 As shown in Example 6.

[0092] Example 7

[0093] 1) Preparation of Example 7 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.110 g hydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a hydroquinone additive electrolyte.

[0094] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an active area of ​​1 cm -2 , thickness is 6mm on graphite felt, conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0095] 3) Preparation of zinc negative electrode sheet: Cut commercial zinc foil into pieces with an active area of ​​1 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0096] 4) Preparation of static electrolytic cell battery: The electrolyte of Example 7 prepared above was added into the electrolytic cell. The positive electrode sheet and the zinc negative electrode sheet were respectively mounted on the platinum metal electrode clip to obtain a static electrolytic cell battery.

[0097] 5) Static electrolytic cell battery test: Using the Xinwei battery test system, at 10mA / cm 2 , 10mAh / cm 2 The static electrolyzer battery was tested under the charge and discharge regime, such as Figure 6 As shown in Example 7.

[0098] Example 8

[0099] 1) Preparation of Example 8 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 47 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.110 g hydroquinone powder to obtain solution B. 3 mL of solution B was added to solution A to obtain a hydroquinone additive electrolyte.

[0100] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an active area of ​​1 cm -2 , thickness is 6mm on graphite felt, conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0101] 3) Preparation of zinc negative electrode sheet: Cut commercial zinc foil into pieces with an active area of ​​1 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0102] 4) Preparation of static electrolytic cell battery: The electrolyte of Example 8 prepared above was added into the electrolytic cell. The positive electrode sheet and the zinc negative electrode sheet were respectively mounted on the platinum metal electrode clip to obtain a static electrolytic cell battery.

[0103] 5) Static electrolytic cell battery test: Using the Xinwei battery test system, at 10mA / cm 2 , 10mAh / cm 2 The static electrolyzer battery was tested under the charge and discharge regime, such as Figure 6 As shown in Example 8. Figure 6 The results showed that the optimal addition concentration of phenolic organic matter was 0.002 mol / L.

[0104] Example 9

[0105] 1) Preparation of Example 9 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.138 g 2,6-dimethylhydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a 2,6-dimethylhydroquinone additive electrolyte.

[0106] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​80 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0107] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut into pieces with an area of ​​84 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0108] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (80 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 84cm 2 ), heat shrink film, aluminum plastic film Figure 2The battery is assembled by stacking the zinc negative electrode, separator (with electrolyte added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (with electrolyte added), and zinc negative electrode in this order, and then putting them into heat shrink film for heating, so that the heat shrink film is tightly attached to the battery cell to obtain a single-layer battery cell. Two battery cells are stacked and put into aluminum-plastic film to obtain a soft-pack battery.

[0109] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, at 8.3mA / cm 2 The soft pack battery was tested at a current density of Figure 7 As shown in Example 9, after 50 cycles, the capacity retention rate can reach 99%, and the capacity retention rate = (50th cycle capacity / maximum capacity within 50 cycles). The voltage capacity of the soft pack battery in Example 9 is as follows: Figure 8 As shown, it has a stable discharge platform, which illustrates the promoting effect of 2,6-dimethylhydroquinone additive electrolyte on the cycle performance of aqueous zinc-manganese batteries.

[0110] Example 10

[0111] 1) Preparation of Example 10 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, 2 mol / L potassium chloride and 0.002 mol / L 2,6-dimethylhydroquinone): 48 mL of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate and 2 mol / L potassium chloride solution A. 20 mL of deionized water was added to 0.138 g 2,6-dimethylhydroquinone powder to obtain solution B. 2 mL of solution B was added to solution A to obtain a 2,6-dimethylhydroquinone additive electrolyte.

[0112] 2) Preparation of positive electrode sheet: Superconducting carbon black (super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​80 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0113] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut into pieces with an area of ​​84 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0114] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (80 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 84cm 2), heat shrink film, aluminum plastic film Figure 2 The assembly is performed by stacking the zinc negative electrode, separator (with electrolyte added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (with electrolyte added), and zinc negative electrode in this order, and then putting them into a heat shrink film for heating so that the heat shrink film is tightly attached to the battery cell to obtain a single-layer battery cell. The three battery cells are stacked and packaged in an aluminum-plastic film to obtain a soft-pack battery.

[0115] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, at 9.3mA / cm 2 The soft pack battery was tested at a current density of Fig. 9 As shown in Example 4. After 30 cycles, the capacity retention rate can reach 95%, and the capacity retention rate = (30th cycle capacity / maximum capacity within 30 cycles). The voltage-capacity curve of Example 10 is shown in Fig.10 As shown, it has a stable discharge platform, which further illustrates the promoting effect of 2,6-dimethylhydroquinone on ampere-hour-level aqueous zinc-manganese soft-pack batteries.

[0116] Comparative Example 1

[0117] 1) Preparation of comparative example 1 electrolyte (concentrations of 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, and 2 mol / L potassium chloride): 50 ml of deionized water was added to a mixture of 10.8 g zinc acetate, 18.3 g manganese acetate, and 7.45 g potassium chloride to obtain 1.5 mol / L manganese acetate, 1 mol / L zinc acetate, and 2 mol / L potassium chloride to obtain an electrolyte.

[0118] 2) Preparation of positive electrode sheet: Superconducting carbon black (Super P) and PVDF binder were mixed and ground evenly at a ratio of 10:1, and a certain amount of NMP dispersion was added and evenly dripped on an area of ​​25 cm -2 , on 1mm thick graphite felt, the conductive carbon loading is 7mg / cm -2 , and then taken out after drying at 70 degrees Celsius for 24 hours to obtain the positive electrode sheet.

[0119] 3) Preparation of zinc negative electrode sheet: Cut the commercial zinc foil into a sheet with an area of ​​27 cm 2 , zinc metal negative electrode sheet with a thickness of 0.6mm.

[0120] 4) Preparation of soft pack battery: The electrolyte, positive electrode sheet and titanium foil (25 cm 2 , 20μm) zinc negative electrode sheet, Whatman GF / A glass fiber separator (area 27cm 2 ), heat shrink film, aluminum plastic film Figure 2The battery is assembled by stacking the zinc negative electrode, separator (electrolyte has been added), carbon felt positive electrode, titanium foil, carbon felt positive electrode, separator (electrolyte has been added), and zinc negative electrode in this order, placing them in a heat shrinkable film and heating them so that the heat shrinkable film fits tightly and fixes the battery cell, and then sealing them in an aluminum-plastic film to obtain a soft-pack battery.

[0121] 5) Testing of soft pack batteries: Using the Xinwei battery testing system, at 4mA / cm 2 The soft pack battery was tested at a current density of Figure 4 As shown in Comparative Example 1.

[0122] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention are still within the scope of protection of the present invention.

Claims

1. A phenol electrolyte for an electrolytic aqueous zinc-manganese battery, characterized in that: The electrolyte is composed of a mixed aqueous solution of zinc acetate, manganese acetate, potassium chloride and phenolic organic matter, and the concentrations of the components are: 0.5-3 mol / L of manganese acetate, 0.5-2 mol / L of zinc acetate, 1-3 mol / L of potassium chloride, and 0.0005-0.01 mol / L of phenolic organic matter. The phenolic organic matter is one or more of hydroquinone, 2-methylhydroquinone, 2,6-dimethylhydroquinone, 2,3,5-trimethylhydroquinone, tert-butylhydroquinone, 2-methoxyhydroquinone and 2,5-dihydroxybiphenyl.

2. The phenol electrolyte for electrolytic aqueous zinc-manganese battery according to claim 1, characterized in that: The concentrations of each component are: zinc acetate 1 mol / L, manganese acetate 1.5 mol / L, potassium chloride 2 mol / L and phenolic organic matter 0.002 mol / L.

3. A method for preparing the phenol electrolyte for electrolytic aqueous zinc-manganese battery according to claim 1 or 2, characterized in that: The steps include: 1) adding deionized water to a mixture of manganese acetate, zinc acetate and potassium chloride to obtain solution A; 2) adding deionized water to the phenol compound powder to obtain solution B; 3) ultrasonically dispersing solution A and solution B to obtain a clear solution; 4) A certain amount of solution B is added to solution A, and the mixture is mixed and dispersed uniformly to obtain solution C; solution C is a phenol electrolyte for electrolytic aqueous zinc-manganese batteries.

4. Use of a phenol electrolyte for an electrolytic aqueous zinc-manganese battery as claimed in claim 1 or 2 in a soft-pack battery.

5. The use of a phenol electrolyte for an electrolytic aqueous zinc-manganese battery in a soft-pack battery as claimed in claim 4, characterized in that: The steps include: 1) preparing a positive electrode sheet; 2) Preparation of zinc negative electrode sheet: 3) Preparing a soft-pack battery: adding a phenol electrolyte for an electrolytic aqueous zinc-manganese battery into a glass fiber separator to obtain a separator with added electrolyte, and matching it with a negative electrode sheet, a positive electrode sheet, a titanium foil, a heat shrinkable film and an aluminum-plastic film. The assembly and stacking order is a negative electrode sheet, a separator with added electrolyte, a positive electrode sheet, a titanium foil, a positive electrode sheet, a separator with added electrolyte, and a negative electrode sheet to obtain a single zinc-manganese soft-pack battery cell, and then the cell is packaged with an aluminum-plastic film to prepare a soft-pack battery.

6. The use of a phenol electrolyte for an electrolytic aqueous zinc-manganese battery in a soft-pack battery as claimed in claim 5, characterized in that: The positive electrode sheet is prepared by: preparing a dispersion A of conductive carbon and polyvinylidene fluoride binder in N-methylpyrrolidone; wherein the mass ratio of the conductive carbon to the polyvinylidene fluoride binder is (1-20):1, and the mass ratio of the solute to the solvent in the dispersion A is 1 / 50-1 / 70; dropping the dispersion A into the positive electrode carbon material until saturated, and drying until the dispersion solvent N-methylpyrrolidone is completely removed to obtain a positive electrode; The conductive carbon includes one or more of activated carbon, carbon micron, nanofiber, carbon nanotube, carbon sphere, Ketjen black and conductive carbon black; The positive electrode carbon material is one or more of carbon felt, graphite felt, graphite, graphene, carbon cloth, and carbon paper.

7. The use of a phenol electrolyte for an electrolytic aqueous zinc-manganese battery in a soft-pack battery as claimed in claim 5, characterized in that: The method for preparing the zinc negative electrode sheet is as follows: cutting commercial zinc foil to obtain the zinc metal negative electrode sheet.

8. A soft-pack battery obtained by applying the phenol electrolyte for electrolytic aqueous zinc-manganese battery as claimed in any one of claims 4 to 7 to a soft-pack battery.

Citation Information

Patent Citations

  • Aqueous electrolyte and aqueous electrolytic MnO2-Zn battery

    CN113054264B

  • Aqueous composite mechanism type zinc-manganese battery

    CN116525973A

  • Preparation method and application of ZnMnO3 nano particles

    CN109835954A

  • Rechargeable aqueous zinc-manganese battery and assembling method thereof

    CN114300669A

  • Modified polyphenylene sulfide, solid-state diaphragm, ampere-hour-grade zinc-manganese secondary battery and manufacturing and formation method of ampere-hour-grade zinc-manganese secondary battery

    CN117264212A